Effects of core stability and calf raise training on lower limb power in adolescent volleyball players: A quasi-experimental study - Taufik Kencana Aji; Setiyawan Setiyawan; Yulia Ratimiasih (Universitas Sriwijaya, 2026)
Research Background: Volleyball requires good lower limb power for jumping during smashes and blocks. However, school training programs tend to focus more on basic techniques than physical conditioning, so leg power is not optimally developed. Research Objective: This study aims to examine and compare the effects of core stability and calf raise training on lower limb power. Method: This study used a quasi-experimental design with two groups (pretest-posttest). The sample consisted of 30 male students aged 13–15 years, divided into two groups. The training program was conducted for 4 weeks (3 sessions per week). Lower limb power was measured using the vertical jump test. Data were analyzed using paired and independent sample t-tests (α = 0.05). Results: Both groups showed significant improvement. The core stability group improved by 2.2, while the calf raise group improved by 4.47. However, there was no significant difference between the two groups (p > 0.05). Conclusion: Both core stability and calf raise training are effective in improving lower limb power and can be used as alternative training methods in school volleyball extracurricular programs.